)Qæ(NDEÇ k(B. (Nd(B. (Nu[INSXKOGO W KONTEKSTÆ SU^ASNOÇ PEDAGOGÆ^NOÇ NAUKI TA OSWÆTI(B: 1991-2009 (NRR(B. :s)E (NDO (B185 (NR)QÆ^^Q WÆD DNQ NARODVENNQ (B: (NBÆBLÆOGR(B. (NPOKAV^(B.s)E - (NrOGOWA(B, (NpAWLA )QæWANÆWNAs)E ((NoDESA(B,s, 2010)
(Nu POKAV^IKU PREDSTAWLENO B)QÆBLÆOGRAFÆ@ PRACX k(B. (Nd(B. (Nu[INSXKOGO(B, (N]O WIDANÆ Z (B80-(NH ROKÆW hh ST(B. (NDO (B2009 (NROKU(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (Nu[INSXKIJ k(B. (Nd(B.s; )Qæ(NSTORÆQ OSWÆTIs)E -- )Qæ(NSTORÆQ PEDAGOGÆ^NOÇ DUMKIs)E; (Nb)QÆBLÆOGRAFÆQs)E; (NB)QÆOGRAFÆQs)E; (NPRAC)QÆs)E; (NPEDAGOGs; (ND)QÆQLXNÆSTXs)E; (NWIHOWANNQs; (NNAW^ANNQs; (NB)QÆBLÆOGRAFÆ^NIJ POKAV^IKs)E